AUDIT COMMITTEE ATTRIBUTES AND THE VALUE OF FIRM: EVIDENCE FROM LISTED INSURANCE COMPANIES IN NIGERIA (Journal of Contemporary Issues in Accounting, 2021)
This study investigated the relationship between audit committee attributes and the value of the firm of listed insurance companies in Nigeria. In order to do this, three research questions were raised and three hypotheses were formulated. Data of audit committee attributes (audit committee independence, audit committee size and audit committee remuneration) and firm value (Tobin’s Q) were obtained from the Nigerian Stock Exchange fact-book, and annual reports and accounts the listed insurance companies on the Nigerian Stock Exchange from 2012-2019. Data obtained were analyzed using both descriptive and inferential statistical tools. Findings of the regression result revealed that while audit committee independence significantly and positively affects the value of the firm, audit committee remuneration and audit committee size negatively and insignificantly affect the value of the firm of insurance companies in Nigeria. Given the findings of the study, it was recommended among others that stakeholders and management should exhibit a positive attitude towards the audit committee attributes by ensuring their independence without interference in their duty or responsibilities. Again, there is the need to increase the audit committee size of listed insurance companies in order to ensure enhanced value of the
Keywords: Audit committee attributes; Firm value; Tobin’s Q; Audit committee independence; Audit committee size; Audit committee